Aphasia and other acquired neurogenic language disorders : a guide for clinical excellence - Hallowell, Brooke (San Diego, CA : Plural Publishing Inc., 2023)
'Covering an array of evidence-based content, including aphasia, traumatic brain injury, dementia, and language in aging, Aphasia and Other Acquired Neurogenic Language Disorders: A Guide for Clinical Excellence, Second Edition is a must-have textbook for clinicians and students studying to be speech-language pathologists. This clinical guide strategically addresses scientific foundations, service delivery, international and multicultural perspectives, assessment, and treatment. Organized to maximize adult learning, the book is adaptable for multiple pedagogic methods for classroom-based courses, independent study, and online learning. The second edition of Aphasia and Other Acquired Neurogenic Language Disorders: A Guide for Clinical Excellence provides clinicians and students a clear pathway for quality and effectiveness in clinical practice'--
Includes bibliographical references (pages 509-574) and index.
Keywords: Language Disorders -- physiopathology; Language Disorders -- therapy; Language Disorders -- diagnosis; Clinical Competence; Evidence-Based Practice